Realidad Aumentada del Conocimiento del Medio Ambiente Social en el salón de clases de Primaria - Verónica Marín-Díaz; Begoña Esther Sampedro-Requena; Juan Manuel Muñoz-González (Revista Caribeña de Investigación Educativa, 2020)
The increased use of information and communication technologies is now a reality that cannot be ignored. The portals, blogs, videos, etc., that we can find on the internet about positive experiences of their use show that the teacher-mediated use of them can turn the curriculum into something that is more attractive to students. Therefore, subjects such as Mathematics, which have a significant degree of complexity for some students, can become appealing and “simple”. One of the so-called emergent technologies, which day by day has become more evident, is Augmented Reality. Saddled between virtual reality and scenic realism, its addition to classroom methodologies implies the possibility of experiencing the content first-hand. In this article, we present the results of a teaching innovation experiment conducted with Primary School students in Spain. Through the “Augment” program, the specific content named “The machines” was developed. This content corresponded to the school subject of Sciences. The starting hypothesis consisted on the use of Augmented Reality for the consolidation of content explained in the traditional manner. Afterwards, the students evaluated the experience developed. The main result obtained is the positive scoring of the tool by the students. Thus, we can conclude, plausibly, that its use in the classroom facilitates the learning of complex content.